Propuesta para la reutilización de aguas residuales del proceso de recubrimientos electrolíticos de la empresa Zintepec Ltda. (2018)
The present project exposes the proposal of reuse of the residual water of the processes of electrolytic coatings of the company ZINTEPEC LTDA, to reduce the water consumption in the rinses and comply with Resolution 1207 of 2014 for the maximum limits allowed for industrial use in heat exchange in cooling towers and boilers, , as well as Resolution 631 of 2015 for the maximum limits allowed in the manufacture of machinery and equipment (Electrolytic Coating). For the development of this project, the diagnosis of the wastewater is made, which contains the description of the processes carried out in the company, the water balance that determines the volume to be reused and the characterization of the residual water that shows the non-compliance with the established parameters for the resolutions. It was established in this way that the volume of water to be reused is 1.73 m3, which does not comply with the current resolutions with the following parameters: 24.6 mg CN / L of total cyanide, 2.43 mg Cu / L of copper , 32.46 mg Cr / L of chromium, 45.47 mg Fe / L of iron, 20.60 mg Ni / L of nickel, 4.06 units of pH, 200.75 mg Zn / L of zinc, 1154 mg O2 / L of DQO and 900 mg O2 / L of DBO5.